Karakteristik fasad bangunan Indis di kawasan Jalan Prawitotaman Yogyakarta - Dessy Anggraini; Dwita Hadi Rahmi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Façade characteristics of Indich buildings in Jalan Prawirotaman Yogyakarta Prawirotaman, Yogyakarta has a unique characteristic with the facade of Indich buildings which used to be the house for Kraton warriors and continued to grow, so that many new buildings emerged with a modern style that could eliminate identity and characteristics in the Jalan Prawirotaman area. Therefore, we need a comprehension of the façade characteristics for Indich buildings so that it can be used as an idea in the design of buildings in the future. This study uses the rationalistic paradigm with qualitative deductive methods. The results of the study show types in each element and the most dominant types including limasan roof with the addition of a small roof (due to the addition of the front room) with clay tile, concrete material walls with cream or white color, the door uses 2 door leaves wood material combination glass rayban, glass massif window, elevation of the floor between 20-60 cm (requires stairs for access) and dominated by one-story buildings. Facade pattern of the entire Indich buildings in the Jalan Prawirotaman area has an asymmetrical pattern but seems balanced and ornaments in the building are in the ventilation, while the column with firm lines and concrete material elements shows the different characteristics variables from the characteristics Indich building basic theory. Examples of the different elements are the windows and building patterns because of the current development and changed by building owners. © 2019 Dessy Anggraini, Dwita Hadi Rahmi